THE EFFECT OF THE DEMONSTRATION METHOD ON THE LEARNING OUTCOMES OF CLASS V STUDENTS OF SDN 071056 TETEHOSI ON PKN SUBJECT - Ndruru, Lestina; Ulil Azmi (PT. Antis International Publisher, 2025)
Objective: This improvement in class IV of SDN 071056 Tetehosi aims to explain how the demonstration method contributes to improving learning outcomes in PKN subject with the topic of the application of Pancasila values in elementary school students in the 2024/2025 academic year. Method : In the learning activity scheme, the first activity lasts for ten minutes. It starts with greeting students, creating a comfortable classroom environment, and making learning tools and teaching aids. The core activity lasts for fifty minutes by delivering learning materials, and the last exercise lasts for ten minutes. The purpose of this exercise is to (a) reinforce the tasks that students completed while working on the LKS. b) Follow the learning objectives that have been set. c) In addition, students are given school assignments. Results : In the study, class IV students at SD Negeri 071056 Tetehosi showed less active in participating in the lesson and did not understand the concept of the lesson. The contributing factor is the use of inappropriate learning methods. Therefore, the learning methods that have been used are improved. Thus, the author can conclude that the application of learning methods determines student activeness in learning. Novelty : The study specifically addresses the integration of the demonstration method with the topic of Pancasila values in elementary school students during the 2024/2025 academic year—highlighting a current and practical effort to align civic education with engaging pedagogical strategies in real classroom settings.